Psychotherapeutic approaches: hopefully, globally effective - Howe, Edmund (Frontiers in Psychiatry, 2024)
SCOPE: I am submitting this piece as Guest Editor of the upcoming issue on Ethical Issues in Psychiatry throughout The World (my paraphrase). This piece is intended to give an overall view of challenges, general and special interventions and controversial issues that may be relevant to maximizing the treatment of all patients throughout the world at this time. Since the pieces accepted at this time tend to deal with particular cultures, this piece is intended to give an overall framework such that the other individual pieces in this issue could be nested upon these overall concepts. Among your possibilities, this would best fit under Policy and Practice Recommendations. (12,000 words) I have adapted the 5 sections to your format, though have also included a different format (same no of words) that may work better if you are accepting of this. I include then as addenda: 1.